Cellular and animal models for high-throughput screening of therapeutic agents for the treatment of the diseases of the elderly in general and Alzheimer’s disease in particular† - Holtzman, Jordan L. (Frontiers in Pharmacology, 2013)
It is currently thought that the dementia of Alzheimer’s disease is due to the neurotoxicity of the deposits or aggregates of amyloid-β (Aβ). Drug discovery has employed mice tranfected with mutant genes responsible for early onset Alzheimer’s disease. Yet, nine trials of drugs that were effective in transgenic mice were ineffective in patients. Further, a major unresolved issue is that Aβ is produced in everyone but deposits are only seen in the elderly. Our published studies indicate that in CSF Aβ is only present as a complex with two chaperones, ERp57 and calreticulin and is N-glycosylated thereby keeping Aβ in solution. This complex formation is catalyzed by the posttranslational protein processing system of the endoplasmic reticulum (ER). These findings suggest that both plaque and dementia are secondary to an age related decline in the capacity of the ER to catalyze the processing of the synaptic membrane proteins necessary for memory. In support of this paradigm components of this ER pathway decline with age. Our observations also suggest that declining ER function has a role in a loss of mitochondrial function and a decrease in myelin. Finally, our findings suggest new cellular and animals models for drug discovery.